Supplements for Devonian–Carboniferous extension and Eurekan inversion along an inherited WNW–ESE-striking fault system in Billefjorden, Svalbard - Koehl, Jean-Baptiste P.; Allaart, Lis; Noormets, Riko (DataverseNO, 2023)
Supplementary data for Devonian–Carboniferous extension and Eurekan inversion along an inherited WNW–ESE-striking fault system in Billefjorden, Svalbard. Content: -S1: Description of the late Paleozoic sedimentary successions in central Spitsbergen from the literature. -S2: (a) Uninterpreted bathymetric data in Billefjorden and (b–d) associated zooms. -S3: Interpreted seismic sections in Billefjorden showing early Cenozoic duplexes and thrusts (yellow lines), bedding surfaces (dotted white lines) and potential multiples (dashed yellow lines). See Fig. 1 for location. (a) SSW-directed Cenozoic thrust between Phantomodden and Narveneset showing (from south to north) in the southern part a well-developed SSW-verging ramp anticline and an open, symmetric, NNE-tilted detachment/ramp anticline. (b) Top-west to top-west thrust sheet with minor reverse offsets. -S4: Uninterpreted seismic sections in Billefjorden. See S1 for location. -S5: Description and interpretation of the upper Paleozoic sedimentary successions on seismic data in Billefjorden. -Lower Devonian sedimentary rocks of the Siktefjellet and Red Bay and Andrée Land groups -Uppermost Devonian to Mississippian sedimentary rocks (Billefjorden Group) -Pennsylvanian to Permian sedimentary rocks (Gipsdalen Group) -Uppermost Mississippian to Lower Pennsylvanian Hultberget and Ebbadalen formations -Middle to lowermost Upper Pennsylvanian Minkinfjellet Formation -Uppermost Middle Pennsylvanian to lowermost Permian Wordiekammen Formation -Lower Permian Gipshuken Formation -S6: Depth conversion data including checkshot data from exploration well 7816/12-1 in Reindalspasset (upper left table; Eide et al., 1991), the depth of lithostratigraphic intervals from the well completion report (upper right table), the depth of formations of interest to the present study from the well completion report (middle right table), average velocities of stratigraphic intervals of interest to the present study from Gernigon et al. (2018; lower right table), and calculated stratigraphic ...